2019
DOI: 10.1080/09669582.2019.1607359
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable accessibility in rural destinations: a public transport network approach

Abstract: There can be no sustainable tourism development without sustainable mobility, which is contingent on informed planning and policy. In rural regions, tourist attractions are spatially scattered, and poor transport planning translates into lower accessibility for non-driving visitors, yet few sustainable planning tools are available for non-urban tourism contexts. This paper seeks to fill this gap by combining advances in transport geography, rural transport, and transport for tourism, and we develop an original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…A more sophisticated analysis by found the scope to improve sustainable transport provision at destinations through understanding visitor practices, associated travel skills, and preferences for the needs of some visitors more than others. Tomej (2020) found that in rural areas, tourist attractions are spatially scattered and public transport is a more sustainable option for mobility.…”
Section: The Aegean Highway 231 Deucalionoachian Ark (Dna)mentioning
confidence: 99%
“…A more sophisticated analysis by found the scope to improve sustainable transport provision at destinations through understanding visitor practices, associated travel skills, and preferences for the needs of some visitors more than others. Tomej (2020) found that in rural areas, tourist attractions are spatially scattered and public transport is a more sustainable option for mobility.…”
Section: The Aegean Highway 231 Deucalionoachian Ark (Dna)mentioning
confidence: 99%
“…Studies on the topic of environmental sustainability can be divided into those that specifically deal with sustainability in terms of "physical environment" (7.9%) and those that explore sustainability concerning "ecological environment" (17.1%). First, studies related to "physical environment" analyze the transportation accessibility and transportation systems that increase the sustainability of rural tourism [85,86], cases of rural tourism used as a tool to increase the sustainability of agricultural land [87], and studies on developing the ways to preserve and promote cultural heritage in a rural area [88][89][90]. The second sub-topic in terms of environment is the "ecological environment".…”
Section: Environmentalmentioning
confidence: 99%
“…Thirdly, by improving the flexibility of public transport and offering services on-demand, transportation systems can be designed to respond directly to the specific geographic and social characteristics of the local area [32,97]. For example, in some areas, such as those with large numbers of tourists, conventional public transport with fixed schedules and timetables may be more advantageous [28,110]. In addition, in areas with higher numbers of people unable to operate a vehicle, car sharing schemes should be limited in favor of more flexible routes and timetables [111].…”
Section: Spatial and Temporal Dimensionsmentioning
confidence: 99%